Total serum IgG and respiratory symptoms as determinants of occupational exposure to the microbial contaminants in metalworking fluids among machining industry workers - Hashim, Nurul Maizura; Hashim, Zailina; Awang Hamat, Rukman (Wolters Kluwer-Medknow, 2017)
Background: Metalworking fluids (MWFs) are commonly used during metalworking processes in the machining industry. Aims: This study was to determine the relationship between total serum immunoglobulin G (IgG) levels with the exposure to microorganisms among workers using MWFs and also to study associations between health symptoms with total IgG. Setting and Design: This cross-sectional study was carried out on 138 machine workers who were exposed to MWFs. Materials and Methods: Respondents were invited to participate in blood sampling for the total serum IgG level analysis. The microbial assessments were carried out on the MWF bulk samples and the aerosols in the air. The data were analyzed using the Statistical Package for the Social Sciences version 22.0. Results: The findings showed significant difference between work sections for serum IgG level (p value = 0.04). The environmental bacteria level had a significant correlation with the total serum IgG level (p value = 0.003). There were also significant relationships between body mass index (BMI) (p value = 0.044), work duration (p value = 0.014), smoking (p value = 0.014), and environmental contaminants (p value = 0.049), with the total serum IgG levels. Health symptoms, such as cough (p value = 0.031), wheezing (p value = 0.043), skin itching (p value = 0.033), and skin redness (p value = 0.005), also related with the total serum IgG levels. Conclusion: There were significant correlations between the total serum IgG levels with microbial contaminants of MWF in metalworking processes. Work duration, smoking, BMI, and environmental contaminants, and health symptoms of cough, skin itching, and inflammation significantly influenced the total serum IgG levels. Total serum IgG antibodies may serve as an indicator of occupational exposure to the microbial contaminants in MWF.